Pelatihan Penggunaan Microsoft Word Pada Siswa Kelas 5 di SD Inpres Tello Baru I/1 - Suharti Sirajuddin; Siti Hafni Kastella; Reski Lili (Yayasan Habiburrahman Jamalu Bina Ummat, 2023)
The development of science and technology that is increasingly advanced in the current era has a good impact on the teaching and learning process, learning can be combined with technology. One of the educational technologies that can help students in the teaching and learning process is Microsoft Word. This application helps students to complete their assignments. Especially in today's modern era, students are required to master and be able to use Microsoft Word. However, based on observations, the use of Microsoft Word is still uneven and has not been prioritized in several schools, one of which is at SD Inpres Tello Baru I/1. This is because teachers tend to use books as learning media and very rarely use technology in learning because technology is considered not to have an important role in the teaching and learning process. This causes students to not be able to master technology, especially in terms of using Microsoft Word. Seeing this situation, training activities on the use of Microsoft Word need to be carried out at SD Inpres Tello Baru I/1. This training activity uses a descriptive method. Through this activity, students are able to master and use Microsoft Word. It is hoped that after participating in this training activity, students can continue to practice using Microsoft Word so that their skills in processing text can continue to improve